Underwater Acoustic Communication (UWA) Data Packet Size Optimization based on Throughput - VIRAKRAINGSEI, HAI SOCHEAT (2010)
The aim of this project is to obtain a new method which will help to maximize the performance of the Underwater Water Acoustic Network. The metrics that will be used namely are Throughput, Bit Error Rate, and Energy. These three metrics are very crucial for the network life time. Throughput will be discussed heaver. Various mathematical methods such as interpolation will be address in order to justify between these three metrics. The main contribution of this project is the algorithm and the lookup table construction developed for selecting optimal packet size in underwater communication efficiency.